A Systematic Literature Review on the Effectiveness of Customer Relationship Management in Building Customer Loyalty in the Digital Era - Aria Syaiful Akbar; Sri Setyo Iriani; Sanaji Sanaji (JPEKA: Jurnal Pendidikan Ekonomi, Manajemen dan Keuangan, 2025)
Despite the widespread use of CRM, evidence regarding its consistent effect on customer loyalty remains fragmented. The rapid development of the virtual world today is very worthy of consideration for a business to immediately build relationships with customers. This study aims to analyze the influence of customer relationship management on customer loyalty within the company. This study uses a literature review method. The data used comes from the outcomes obtained from the research that has been conducted and published in national journals accredited by SINTA. This review applied a qualitative content analysis of 21 SINTA-indexed articles published between 2020–2025. The steps of data analysis are: data collection, data reduction, data presentation, and conclusions. The research results and discussion indicate that CRM has a positive and meaningful impact on customer loyalty within a company. The more effective or appealing the CRM program implemented, the higher the customer loyalty. CRM helps gain a better understanding of customers and can provide more personalized service tailored to individual needs, thus strengthening loyalty. CRM is crucial for building, maintaining, and enhancing strong relationships with customers, as it can provide significant opportunities for companies to increase long-term profits. In conclusion, the implementation of CRM can maintain the existence of a company's business in the long term and can maintain and increase customer loyalty so that they do not switch to competitors. This study identifies dominant CRM dimensions affecting loyalty and highlights gaps for future empirical investigation.